A novel phylogenetic infrageneric classification of Baccharis (Asteraceae: Astereae), a highly diversified American genus. Issue 5 (25th November 2019) - Heiden, Gustavo; Antonelli, Alexandre; Pirani, José Rubens
Abstract: We present the hitherto most comprehensive phylogenetic hypothesis for Baccharis . Our results confirm that subtribe Baccharidinae is a monogeneric group and support a broad circumscription of Baccharis as monophyletic with the inclusion of all genera that have been previously segregated from it ( Baccharidastrum, Baccharidiopsis, Heterothalamulopsis, Heterothalamus, Lanugothamnus ). We provide comprehensive lists of accepted and synonymized infrageneric taxa. Seven main lineages are recognized, which we treat as subgenera. Subgenera Baccharis and Molina roughly match previous circumscriptions, while subgenera Pteronioides and Stephananthus are merged with Molina . In total, we propose that Baccharis comprises 440 species classified into 7 subgenera and 47 sections, while 22 sections are considered synonyms. The phylogeny provided constitutes the basis for further exploration of the evolutionary processes that have allowed the group to attain its wide geographic distribution, morphological variation, variable sexual reproductive strategies, and complex chemical contents.